Fabrication and characterisation of a silicon-borosilicate glass microfluidic device for synchrotron-based hard X-ray spectroscopy studies. Issue 47 (7th September 2021) - Micheal Raj, Pushparani; Barbe, Laurent; Andersson, Martin; De Albuquerque Moreira, Milena; Haase, Dörthe; Wootton, James; Nehzati, Susan; Terry, Ann E.; Friel, Ross J.; Tenje, Maria; Sigfridsson Clauss, Kajsa G. V.
Abstract : Left – A schematic view of the XAS microfluidic set up at the beamline; fluorescence detector at 90° angle to the X-ray beam (green line); right – microfluidic device setup on Balder beamline mounted perpendicular to beam path. Abstract : Some of the most fundamental chemical building blocks of life on Earth are the metal elements. X-ray absorption spectroscopy (XAS) is an element-specific technique that can analyse the local atomic and electronic structure of, for example, the active sites in catalysts and energy materials and allow the metal sites in biological samples to be identified and understood. A microfluidic device capable of withstanding the intense hard X-ray beams of a 4th generation synchrotron and harsh chemical sample conditions is presented in this work. The device is evaluated at the K -edges of iron and bromine and the L 3 -edge of lead, in both transmission and fluorescence mode detection and in a wide range of sample concentrations, as low as 0.001 M. The device is fabricated in silicon and glass with plasma etched microchannels defined in the silicon wafer before anodic bonding of the glass wafer into a complete device. The device is supported with a well-designed printed chip holder that made the microfluidic device portable and easy to handle. The chip holder plays a pivotal role in mounting the delicate microfluidic device on the beamline stage. Testing validated that the device was sufficiently robust to contain and flow through harsh acids and toxic samples. There was also no significant radiation damage to the device observed, despite focusing with intense X-ray beams for multiple hours. The quality of X-ray spectra collected is comparable to that from standard methods; hence we present a robust microfluidic device to analyse liquid samples using synchrotron XAS.